Corporate taxation and corporate governance - Marko Köthenbürger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2009)
The effects of corporate taxation on firm behavior have been extensively discussed in the neoclassical model of firm behavior which abstracts from agency problems. As emphasized by the corporate governance literature, corporate investment behavior is however crucially influenced by diverging interests between shareholders and managers. We set up an agency model and analyze the crucial issue in corporate taxation of whether the normal return on investment should be exempted from taxation. The findings suggest that the divergence of interests may be intensified and welfare reduced if the corporate tax system exempts the normal return on investment from taxation. The optimal system may well use the full return on investment as a tax base. Hence, tax systems such as an Allowance for Corporate Equity (ACE) or a Cash-flow tax do not have the familiar efficiency-enhancing effects in the presence of corporate agency problems.
Keywords: H25; D21; 330; corporate taxation; corporate governance; allowance for corporate equity; comprehensive business income tax; cash flow tax